The Role of the Let’s Read Application in Increasing Reading Interest among Elementary School Children: A Case in South Tangerang - Firdaus Habibi; Erniyanti Nur Fatahhela Dewi (Institut Agama Islam Negeri Palopo, 2025)
The current research aims to investigate the progress of reading habits through Let’s Readapp and explore more the factors affected of the enhancement of reading habits. Further, the research employed a qualitative case study design with a sixth-grade student at SD Negeri Cirende 2, South Tangerang as the key informant. Then, the data were collected through semi-structured interviews and observations, then analyzed descriptively to provide clear insights. Therefore, the research indicated that several factors influenced Vida in her reading habits. For instance, it could be seen from the exposure of reading, reading interests, and the availability of book resources. Additionally, Let’s Read app possessed some substantial roles in Vida’s reading habits, including simple vocabularies for basic learners, learning grammar from the stories, eye-catching pictures, various languages, and a plenty of themes. To sum up, Let’s Read app was able to applied as the effective solution in promoting reading habits for a school-aged child.